KOMPENSASI, BEBAN KERJA, PENGEMBANGAN KARIER, KEPUASAN KERJA DAN PERILAKU CARING PADA PERAWAT RAWAT INAP RSUD KHIDMAT SEHAT AFIAT KOTA DEPOK TAHUN 2023 - Surahman, Aris; Azis, Abdul (Jurnal Penelitian Keperawatan Medik, 2023)
The high rate of uncaring behavior in providing nursing care to patients, to overcome this problem requires improvements in compensation, career development workload and nurse job satisfaction so that caring behavior can be realized. Quantitative method, cross sectional using smartPLS with a population of 90 nurses. The research results show that compensation has a positive effect on job satisfaction, with a t value of 1.990 which is significant at α=5%. Compensation has a positive effect on caring behavior, with a t value of 2.079 and significant at α=5%. Workload has a negative effect on career development, with tcount value is 5.980 and is significant at α=5%, Workload has a negative effect on job satisfaction, with a tcount value of 7.279 and is significant at α=5%, Workload has a negative effect on caring behavior with a tcount value of 1.990 and significant at α= 5%, Career development has a positive effect on job satisfaction, with a t-value of 1.990 and is significant at α=5%, Career development has a positive effect on caring behavior, with a t-count of 3.608 and significant at α=5%, Job satisfaction has a positive effect on caring behavior, with a t value of 2.079 and significant at α=5%, of the four variables studied, the variable that most dominantly influences the caring behavior of inpatient nurses at Khidmat Sehat Afiat Hospital, Depok City is the workload variable with a direct value of 27%. The conclusion of this research is to provide reinforcement so that the workload of nurses is proportionately adjusted to competency so that nurses' caring behavior can increase